Mechanisms of Drug Resistance in Cancer Chemotherapy: Coordinated Role and Regulation of Efflux Transporters and Metabolizing Enzymes - Krishna Vadlapatla, Ramya; Dutt Vadlapudi, Aswani; Pal, Dhananjay; K. Mitra, Ashim (Current Pharmaceutical Design, 2013)
Cancer remains one of the major leading causes of death worldwide. Acquisition of multidrug resistance (MDR) remains a major impediment to successful chemotherapy. As the name implies, MDR is not limited only to one drug but often associated to structurally and functionally unrelated chemotherapeutics. Extensive research and investigations have identified several mechanisms underlying the development of MDR. This process of drug resistance is considered to be multifactorial including decreased drug accumulation, increased efflux, increased biotransformation, drug compartmentalization, modification of drug targets and defects in cellular pathways. In the first part of the review, these pharmacokinetic and pharmacodynamic mechanisms have been described in brief. Although the pathways can act independently, they are more often intertwined. Of the various mechanisms involved, up-regulation of efflux transporters and metabolizing enzymes constitute a major resistance phenotype. This review also provides a general biological overview of important efflux transporters and metabolizing enzymes involved in MDR. Further, synergistic action between efflux transporters and metabolizing enzymes leading to MDR could possibly arise due to two different factors; overlapping substrate specificity and coordinated regulation of their expression. The expression of efflux transporters and metabolizing enzymes is governed by nuclear receptors, mainly pregnane X receptor (PXR). The pharmacological role of PXR and advances in the development of PXR antagonists to overcome MDR are outlined.
Keywords: efflux transporters